Pengaruh Konsumsi Daun Kelor Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Trimester III di Klinik Mutiara Medika Kabupaten Lebak - Cahyaningsih, Intan Dwi; Widyastuti, Wiwin (Universitas Malahayati, 2025)
ABSTRACT Anemia can increase the risk of maternal death, abortion, premature delivery, inhibition of fetal growth and development in the womb, easy to cause infection, antepartum hemorrhage, premature rupture of membranes (KPD), during childbirth can result in His disorder, the first period can last for a long time, and in the postpartum period uterine subinvolution causes postpartum hemorrhage, facilitating puerperium infection and reduced breast milk production. To determine the effect of moringa leaf biscuit consumption on the increase in hemoglobin levels in pregnant women in the third trimester. This study employed a cross-sectional design with a sample size of 19 participants. Data analysis was conducted using univariate analysis through frequency distribution and bivariate analysis with statistical computations performed using the SPSS software. The results of this study showed that the average Hb level of respoden before being given moringa leaf biscuits was 10,189 with a maximum value = 11.5, and a minimum = 8.6, and the average Hb level of respondents after being given moringa leaf biscuits was 11,089 with a maximum value = 12.4, and a minimum = 9.5, so it can be concluded that there is an Effect of Moringa Leaf Consumption on the Increase in Hemoglobin Levels of Pregnant Women at the Mutiara Medika Clinic, Lebak Regency 2024., and there is an effect of moringa leaf consumption on the increase in hemoglobin levels of pregnant women with a p value of 0.000 There is an effect of moringa leaf consumption on the increase in hemoglobin levels of pregnant women in the third trimester. It is recommended that pregnant women can increase their nutritional intake from foods that contain high iron and regularly take blood-boosting tablets to increase Hb levels. Keywords: Nutritional Status, Parity, Number of Children, Breast Milk Production. ABSTRAK Anemia dapat meningkatkan risiko kematian ibu, terjadi abortus, persalinan prematuritas, hambatan tumbuh kembang janin dalam rahim, mudah terjadi infeksi, perdarahan antepartum, ketuban pecah dini (KPD), saat persalinan dapat mengakibatkan gangguan His, kala pertama dapat berlangsung lama, dan pada kala nifas terjadi subinvolusi uteri menimbulkan perdarahan postpartum,memudahkan infeksi puerperium dan pengeluaran ASI berkurang. Untuk mengetahui pengaruh konsumsi biskuit daun kelor terhadap peningkatan kadar hemoglobin pada ibu hamil trimester III. Penelitian ini menggunakan desain pendekatan cross sectional dengan sample 19 orang. Teknik data termasuk dalam analisis univariat menggunakan distribusi frekuensi dan analisis bivariat menggunakan perhitungan statistik program SPSS. Penelitian ini menunjukkan rata-rata kadar Hb responden sebelum mengkonsumsi biskuit daun kelor adalah 10.189, dengan nilai maksimum 11.5 dan minimum 8.6. Setelah mengkonsumsi biskuit daun kelor, rata-rata kadar Hb meningkat menjadi 11.089, dengan nilai maksimum 12.4 dan minimum 9.5. Kesimpulannya, konsumsi daun kelor memiliki pengaruh signifikan terhadap peningkatan kadar hemoglobin ibu hamil di Klinik Mutiara Medika Kabupaten Lebak pada tahun 2024, dengan p-value 0,000. Terdapat pengaruh konsumsi daun kelor terhadap peningkatan kadar hemoglobin ibu hamil trimester III. Disarankan ibu hamil dapat meningkatkan asupan nutrisi dari bahan makanan yang mengandung zat besi yang tinggi dan rutin meminum tablet tambah darah untuk meningkatkan kadar Hb. Kata Kunci: Status Gizi,Paritas,Jumlah Anak,Pengeluaran ASI.